Serum BDNF Levels are Not Associated with the Antidepressant Effects of Nonconvulsive Electrotherapy - Zheng W (Dove Medical Press, 2020)
Wei Zheng,1 Miao-Ling Jiang,1 Hong-Bo He,1 Ri-Peng Li,1 Qi-Long Li,1 Chun-Ping Zhang,1 Su-Miao Zhou,1 Su Yan,1 Yu-Ping Ning,1,2 Xiong Huang1 1The Affiliated Brain Hospital of Guangzhou Medical University (Guangzhou Huiai Hospital), Guangzhou, People’s Republic of China; 2The First School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Xiong Huang; Yu-Ping NingThe Affiliated Brain Hospital of Guangzhou Medical University (Guangzhou Huiai Hospital), 36 Mingxin Road, Liwan District, Guangzhou, People’s Republic of ChinaTel +86-189-22165303; +86-185-10808443Fax +86-20-81778484; +86-20-81891425Email 1195768576@qq.com; ningjeny@126.comObjective: Brain-derived neurotrophic factor (BDNF) has been implicated in the pathophysiology of depression and in the antidepressant response. This study examined whether changes in serum BDNF levels are associated with the antidepressant effects of nonconvulsive electrotherapy (NET).Methods: For BDNF analyses, serum samples were collected from 20 patients with treatment-refractory depression (TRD) and from 20 healthy controls. Serum samples were also collected from patients following a course of NET.Results: Although significantly lower baseline serum BDNF levels were observed in TRD patients than in healthy controls, no changes in serum BDNF levels were found in TRD patients after a course of NET compared to baseline. No significant association was found between serum BDNF levels and depression severity.Conclusion: Serum BDNF levels appear to have no clinical utility in the prediction of the antidepressant effects of NET in patients with TRD. Future studies of higher quality and with larger sample sizes are needed to confirm these findings.Keywords: brain-derived neurotrophic factor, nonconvulsive electrotherapy, treatment-refractory depression